Relationship between body condition score, sub-clinical endometritis and milk yield of dairy cows after parturition - SHARMA, AKSHAY; SINGH, MADHUMEET; KUMAR, PRAVESH; DOGRA, P K (The Indian Journal of Animal Sciences, 2019)
The objective of this study was to diagnose sub-clinical endometritis (SCE) via endometrial cytology on day 42 after parturition and its impact on milk yield (305 days) of dairy cows (parity 2–4). Endometrial cytology was performed in 20 dairy cows, out of which 6 cows were found positive for sub-clinical endometritis. Mean number of polymorphonuclear cells was significantly higher in sub-clinical endometritis positive cows (22.00±4.77%) when compared to cows found negative for sub-clinical endometritis (2.58±0.76%). Sub–clinical endometritis positive cows had a significantly lower (P